PROMISING RESULTS OF INTERNATIONAL COOPERATION IN THE FIELD OF FINE AND APPLIED ARTS OF UZBEKISTAN IN 2020–2026 (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article comprehensively analyzes the processes of international cooperation of the Republic of Uzbekistan in the field of fine and applied arts in 2020–2026. The study covers the theoretical foundations of this cooperation, its role in modern cultural diplomacy, and its impact on the development of national art. The importance of international exhibitions, festivals, creative exchange programs, and joint projects is also assessed on a scientific basis. The article also separately considers new mechanisms for promoting art through digital technologies. The analysis also includes issues of exporting handicraft products to international markets in the field of applied arts. As a result of the study, the role of international cooperation in promoting national art on a global scale was identified. At the same time, existing problems, including limitations related to infrastructure and financial resources, were also revealed. Scientifically based proposals and recommendations were developed to eliminate them. The study also substantiated promising development directions and expected results. This article serves as an important source for scientific research in the fields of art history and cultural studies.